1997
DOI: 10.1016/s0893-133x(97)00034-1
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Phencyclidine Administration Reduces Mesoprefrontal Dopamine Utilization and Impairs Prefrontal Cortical-Dependent Cognition in the Rat

Abstract: Repeated ingestion of phencyclidine by humans induces enduring schizophrenic symptomatology, particularly cognitive dysfunction. In the presently described series of experiments, the neurochemical and cognitive consequences of subchronic phencyclidine administration in the rat were explored. Repeated phencyclidine exposure led to a selective reduction in basal and stress-evoked dopamine utilization in the prefrontal cortex. In addition, rats previously subchronically-treated with phencyclidine were impaired on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
173
2
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(188 citation statements)
references
References 56 publications
10
173
2
2
Order By: Relevance
“…Previously, we showed that subchronic PCP exposure impaired spatial working memory and led to reductions in basal and stress-evoked dopamine utilization in the prefrontal cortex of the rat (Jentsch et al 1997b), and here, we demonstrate that this biochemical effect is enduring (at least 3 weeks), dependent upon repeated exposure to the drug, and induced by longterm NMDA receptor blockade. Furthermore, we show augmented locomotor response to mild stress and amphetamine (using behavioral measures) and haloperidol administration (using ex vivo biochemical measures) in rats after subchronic PCP exposure.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previously, we showed that subchronic PCP exposure impaired spatial working memory and led to reductions in basal and stress-evoked dopamine utilization in the prefrontal cortex of the rat (Jentsch et al 1997b), and here, we demonstrate that this biochemical effect is enduring (at least 3 weeks), dependent upon repeated exposure to the drug, and induced by longterm NMDA receptor blockade. Furthermore, we show augmented locomotor response to mild stress and amphetamine (using behavioral measures) and haloperidol administration (using ex vivo biochemical measures) in rats after subchronic PCP exposure.…”
Section: Discussionsupporting
confidence: 77%
“…The neurochemical effects of mild stress exposure or systemic amphetamine administration on dopamine transmission in the nucleus accumbens are complicated by the fact that these conditions likely increase prefrontal cortical dopamine transmission to some degree in rats repeatedly exposed to PCP, even if the response is reduced as compared to controls (Jentsch et al 1997b). Thus, these situations may lead to a partial reversal of the cortical dopamine dysfunction that presumably propagates the subcortical hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that withdrawal from PCP treatment is associated with an upregulation of 5-HT 2A receptors (Kitaichi et al, , 1999) and a progressive increase in serotonin utilization in the prefrontal cortex, indicating an overstimulation of serotonin neurotransmission in this brain area during withdrawal; the amplitude of this effect is proportional to the duration of the preceding PCP treatment and is reversed by antipsychotic drugs having 5-HT 2A receptor antagonist activity (eg clozapine) (Noda et al, 1995(Noda et al, , 2000Quiao et al, 2001). Moreover, two laboratories showed that during PCP withdrawal, depending on the duration of PCP treatment, there is a progressive decrease in basal-or stress-evoked dopamine utilization in the prefrontal cortex associated with an increase in subcortical dopamine turnover induced by amphetamine or a stressor (Jentsch et al, 1997c(Jentsch et al, , 1998bNoda et al, 2000;Balla et al, 2001). Therefore, sustained PCP exposure seems to establish imbalances between serotonin and dopamine transmission in cortical brain regions as well as in the functioning of these two neurotransmitter systems between cortical and subcortical brain regions that may lead to the expression of a long-lasting dysphoric effect of the drug at the cessation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there are qualitative and quantitative differences in the effects of acute vs chronic PCP exposure (Jentsch and Roth, 1999). For example, studies demonstrated that the chronic treatment selected here has been effective previously in inducing durable cognitive dysfunction, social withdrawal, and enhancement of immobility time in the forced swim test in rats or mice that are not observable after acute PCP (Noda et al, 1995(Noda et al, , 2000Jentsch et al, 1997c;Quiao et al, 2001). Thus, it was important to characterize withdrawal from both high-dose bolus PCP administration and withdrawal from chronic sustained PCP exposure in the ICSS paradigm.…”
Section: Introductionmentioning
confidence: 93%
“…The non-competitive NMDA receptor antagonist, phencyclidine (PCP), is a psychomotor stimulant drug that has been shown to induce symptoms characteristic of schizophrenia [30,31]. PCP and its structural analogue ketamine produce inactivation of inhibitory control by decreasing GABA release [58].…”
Section: Introductionmentioning
confidence: 99%